Behavioral responses of satellite tracked Blainville's beaked whales (Mesoplodon densirostris) to mid‐frequency active sonar. Issue 1 (17th June 2019) - Joyce, Trevor W.; Durban, John W.; Claridge, Diane E.; Dunn, Charlotte A.; Hickmott, Leigh S.; Fearnbach, Holly; Dolan, Karin; Moretti, David
Abstract: The vulnerability of beaked whales (Family: Ziphiidae) to intense sound exposure has led to interest in their behavioral responses to mid‐frequency active sonar (MFAS, 3–8 kHz). Here we present satellite‐transmitting tag movement and dive behavior records from Blainville's beaked whales ( Mesoplodon densirostris ) tagged in advance of naval sonar exercises at the Atlantic Undersea Test and Evaluation Center (AUTEC) in the Bahamas. This represents one of the largest samples of beaked whales individually tracked during sonar operations ( n = 7). The majority of individuals (five of seven) were displaced 28–68 km after the onset of sonar exposure and returned to the AUTEC range 2–4 days after exercises ended. Modeled sound pressure received levels were available during the tracking of four individuals and three of those individuals showed declines from initial maxima of 145–172 dB re 1 μPa to maxima of 70–150 dB re 1 μPa following displacements. Dive behavior data from tags showed a continuation of deep diving activity consistent with foraging during MFAS exposure periods, but also suggested reductions in time spent on deep dives during initial exposure periods. These data provide new insights into behavioral responses to MFAS and have important implications for modeling the population consequences of disturbance.